Lymph node dissection in lung cancer surgery: a comparison between robot-assisted vs. video-assisted thoracoscopic approach - Hurley, Patrick Deniz; Fabbri, Giulia; Berjaoui, Nabih; Patel, Akshay Jatin; Lampridis, Savvas; Routledge, Tom; Bille, Andrea (Frontiers in Surgery, 2024)
Background: TNM staging is the most important prognosticator for non-small cell lung cancer (NSCLC) patients. Staging has significant implications for the treatment modality for these patients. Lymph node dissection in robot-assisted thoracoscopic (RATS) surgery remains an area of ongoing evaluation. In this study, we aim to compare lymph node dissection in RATS and VATS approach for lung resection in NSCLC patients. Methods: We retrospectively compiled a database of 717 patients from July 31, 2015, to July 7, 2022, who underwent either a wedge resection, segmentectomy or lobectomy. We analysed the database according to lymph node dissection. The database was divided into RATS (n = 375) and VATS (n = 342) procedures. Results: The mean number of lymph nodes harvested overall with RATS was 6.1 +/- 1.5 nodes; with VATS approach, it was 5.53 +/- 1.8 nodes. The mean number of N1 stations harvested was 2.66 +/- 0.8 with RATS, 2.36 +/- 0.9 with VATS. RATS approach showed statistically higher lymph node dissection rates compared to VATS (p = 0.002). Out of the 375 RATS procedures, 26 (6.4%) patients undergoing a RATS procedure were upstaged from N0/N1 staging to N2. N0/N1 to N2 upstaging was reported in 28 of 342 (8.2%) patients undergoing a VATS procedure. The majority of upstaging was seen in N0 to N2 disease: 19 of 375 (5%) for RATS and 23 of 342 (6.7%) for VATS. Conclusions: We conclude that in RATS procedures, there is a higher rate of lymph node dissection compared to VATS procedures. Upstaging was mostly seen in N0 to N2 disease, this was observed at a higher rate with VATS procedures.